Issues of drug circulation in a hospital: how to optimize work in a medical information system - A. S. Fedorenko; A. T. Burbello; E. L. Lataria; O. V. Granatovich; M. V. Pokladova (Izdatelstvo OKI, 2022)
Relevance. Currently, the  implementation of information systems in healthcare is an urgent task for every medical organization. The main directions of the introduction of a medical information system in a medical organization are the development of automatic workplaces for specialists, the development of specialized soft ware for decision-making; creation of an electronic medical record and automation of managerial and administrative functions. With the  right management approach to the operation of a medical information system (MIS), a medical organization can use all the possibilities of a MIS to reduce the labor costs of its employees in various areas, for example, in the case of the circulation of drugs. Objective. Show the possibilities of using MIS on the circulation of drugs in a multidisciplinary hospital. Methods. The work was carried out on the basis of the MIS of the North-Western State Medical University named after I. I. Mechnikov of the Ministry of Health of Russia through the introduction of a drug circulation system in a medical organization at various levels (clinical units, a pharmacy, the administration of a medical organization). Results. In the article, on the example of a multidisciplinary medical organization, the results of the implementation of accounting, planning and control over drug supply in the MIS are presented. Conclusion. The joint work of all departments involved in the circulation of drugs (pharmacy warehouse, purchasing department, clinical departments and clinical pharmacologist) allows improving the quality of drug supply and timely obtaining information about the costs and needs for medicines, which optimizes the financial costs of drugs in the hospital.